Collagen and Discoidin Domain Receptor 1 Partnership: A Multifaceted Role in the Regulation of Breast Carcinoma Cell Phenotype - Saby, Charles; Maquoi, Erik; Saltel, Frédéric; Morjani, Hamid (Frontiers in Cell and Developmental Biology, 2021)
Type I collagen, the major components of breast interstitial stroma, is able to regulate breast carcinoma cell behavior. Discoidin domain receptor 1 (DDR1) is a type I collagen receptor playing a key role in this process. In fact, collagen/DDR1 axis is able to trigger the downregulation of cell proliferation and the activation of BIK-mediated apoptosis pathway. The aim of this review is to discuss the role of two important factors that regulate these processes. The first factor is the level of DDR1 expression. DDR1 is highly expressed in epithelial-like breast carcinoma cells, but poorly in basal-like ones. Moreover, DDR1 undergoes cleavage by MT1-MMP, which is highly expressed in basal-like breast carcinoma cells. The second factor is type I collagen remodeling since DDR1 activation depends on its fibrillar organization. Collagen remodeling is involved in the regulation of cell proliferation and apoptosis through age- and proteolysis-related modifications.